2019
DOI: 10.3389/fmicb.2019.02648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Strategies to Reduce Ruminal Protozoa and Their Impacts on Nutrient Utilization and Animal Performance in Ruminants – A Meta-Analysis

Abstract: Several studies have evaluated the effects of complete or partial ruminal protozoa (RP) inhibition; however, to this date, no practical suppressant has been identified and used in large scale. This meta-analysis quantitatively evaluates the effectiveness of multiple strategies on inhibiting RP numbers and their influence on ruminal fermentation and animal performance. This study compared 66 peer-reviewed articles (16 manuscripts for complete and 50 manuscripts for partial RP inhibition that used supplemental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
(85 reference statements)
1
20
0
1
Order By: Relevance
“…Previously, (Ramos-Morales et al 2017) suggested that a persistent effect to depress protozoa can be done by chemical modification of the group that attached to the sapogenin. The type of diet fed to the animal, besides the saponin structure may also affect the antiprotozoal activity of these saponins (Patra and Saxena 2009;Dai and Faciola 2019). In this experiment, types of protozoa that survived in the presence of SRE were not identified, but (Zhou et al 2011) showed that tea saponin could selectively inhibit specific type of protozoa causing reduction of protozoal diversity in the rumen of sheep.…”
Section: Effect Of Sre On Rumen Fermentationmentioning
confidence: 81%
“…Previously, (Ramos-Morales et al 2017) suggested that a persistent effect to depress protozoa can be done by chemical modification of the group that attached to the sapogenin. The type of diet fed to the animal, besides the saponin structure may also affect the antiprotozoal activity of these saponins (Patra and Saxena 2009;Dai and Faciola 2019). In this experiment, types of protozoa that survived in the presence of SRE were not identified, but (Zhou et al 2011) showed that tea saponin could selectively inhibit specific type of protozoa causing reduction of protozoal diversity in the rumen of sheep.…”
Section: Effect Of Sre On Rumen Fermentationmentioning
confidence: 81%
“…The total digestible nutrients were calculated according to NRC [24] using the digestible fractions of nonfiber carbohydrates, crude protein, ether extract, and neutral detergent fiber. The nutrient digestibility coefficient (CD) was determined according to the equation: CD = ((kg of ingested portion − kg of excreted portion)/(kg of ingested portion)) × 100 (1) The nitrogen balance and microbial protein production were evaluated by total urine collection. Total urine collection was carried out in individual bowls containing 50 mL of 20% sulfuric acid solution.…”
Section: Trial 2-nutrient Digestibility Nitrogen Balance and Ingestiv...mentioning
confidence: 99%
“…1 Assurance levels (per kilogram of active elements): 120 g of calcium, 87 g of phosphorus, 147 g of sodium, 18 g of sulfur, 590 mg of copper, 40 mg of cobalt, 20 mg of chromium, 1800 mg of iron, 80 mg of iodine; 1300 mg of manganese, 15 mg of selenium; 3800 mg of zinc, 300 mg of molybdenum; maximum 870 mg of fluoride. 2 NFC = 100 − NDF ap − CP − EE.…”
mentioning
confidence: 99%
“…Newbold et al [40] recommended complete rumen protozoal elimination as a means to increase microbial protein supply by 30% while reducing methane production by up to 11%. However, Dai and Faciola [41] recommended partial rumen protozoal reduction strategies, and tannin supplementation, to reduce methane production. Plant material supplementation resulted in reduced TVFA concentrations, supporting the findings of Min et al [36] concerning lower TVFA concentrations as compared to the control.…”
Section: In Vitro Rumen Fermentation Bacteria and Protozoal Population Characteristicsmentioning
confidence: 99%